2023
DOI: 10.2478/jcbtp-2023-0011
|View full text |Cite
|
Sign up to set email alerts
|

Money Supply Determination Process for Japan

Abstract: This study re-investigates the money supply determination process for Japan. The methodology of this study, which differs from previous studies, is constructed on the assumption of potential nonlinear (asymmetric) relations between money supply and monetary base via money multiplier. To this aim, the nonlinear autoregressive distributed lag (ARDL) model by Shin, Yu and Greenwood-Nimmo, (2014) is applied. This model allows us to examine the endogeneity and exogeneity of the money supply determination process vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Likewise, within the Eurozone, Deleidi and Fontana (2019) found that bank loans affected bank deposits, thereby influencing the monetary base, which is consistent with post-Keynesian theory and lends support to the endogenous viewpoint. Lastly, a recent investigation in Japan by Ongan and Gocer (2023) employing nonlinear models demonstrated that internal factors significantly impact Japan's money supply, enriching our understanding of the endogenous nature of money supply and providing tailored insights into Japan's circumstances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Likewise, within the Eurozone, Deleidi and Fontana (2019) found that bank loans affected bank deposits, thereby influencing the monetary base, which is consistent with post-Keynesian theory and lends support to the endogenous viewpoint. Lastly, a recent investigation in Japan by Ongan and Gocer (2023) employing nonlinear models demonstrated that internal factors significantly impact Japan's money supply, enriching our understanding of the endogenous nature of money supply and providing tailored insights into Japan's circumstances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The money supply is the total amount of money that belongs to all people in a society (Ongan & Gocer, 2023). There are two ways to explain the money supply: a narrow way called M1 and a broader way called M2.…”
Section: The Money Supplymentioning
confidence: 99%